Analisis Tingkat Kesejahteraan Rumah Tangga Petani Padi di Desa Cadaskertajaya Kecamatan Telagasari Kabupaten Karawang - Putri, Anggini Aulia; Azzahra, Fatimah; Fikri, Muhammad Rom Ali (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Agricultural development in rural areas not only increases production, but also increases people's income, opens up more job opportunities, and improves welfare. This research aims to analyze farmer household income, farmer household expenditure, and the level of welfare of rice farmer households in Cadaskertajaya Village, Telagasari District, Karawang Regency. The research method used is Mix Method, with primary and secondary data types. Primary data was collected through interviews using questionnaires from 47 rice farmers. Secondary data was obtained from the Central Statistics Agency, Karawang Regency Agricultural Service, Cadaskertajaya Village, and other institutions. Samples were taken using the proportional random sampling method, with the criteria being farmer owners and farm workers. Data analysis uses the Directorate of Land Use's criteria poverty line for household income, the Sayogyo criteria poverty line for household expenditure, and welfare indicators from BPS. The research results show that the average household income of rice farmers in Cadaskertajaya Village is IDR 34,582,351.69 per year and IDR 8,124,446.81 per capita per year. The household expenditure of rice farmers is IDR 25,380,255.32 per year and IDR 8,413,937.59 per capita per year. Based on the poverty line criteria of the Directorate of Land Use, 53.19% of farmers are not poor, and according to the Sayogyo criteria, 82.61% are not poor. The welfare level is calculated using 11 indicators from BPS, with the highest score being 33 and the lowest score being 27, which is still included in the high welfare category.